A distributed model of collective creativity in free play - Kalaydjian, Juliette; Laroche, Julien; Noy, Lior; Bachrach, Asaf (Frontiers in Education, 2022)
A group of children engaged in free play can spontaneously create new rules, learn to follow them, or find opportunities to break established rules. This rule-playing can be considered as a specific manifestation of the more general phenomenon of collective creativity. In behavioral sciences, collective creativity is often discussed as a collection of individuals each being creative. An alternative perspective views collective creativity as a distributed phenomenon: collective creativity is not a property of an individual agent but rather, it emerges from the interactions within a group (Sawyer, 2014). Approaching free play as a case of distributed collective creativity, we understand rule-playing in terms of two complementary modes: group exploration and group exploitation, and the transition between them. Free play is not easily amenable to fine-grained observational analysis. To overcome this, we developed the Grid Game, a new experimental setup which supports detailed empirical investigation while preserving the essence of free play. The Grid Game is a group improvisation game (Himberg, 2018) that uses the turn taking logic and spatial organization of typical board games, without any other predefined rules. Small groups of kids (4-5 participants) took turns in freely moving or manipulating a provided set of objects on a large 4X4 grid on the floor for 10 minutes, while being video-recorded. Despite the absence of predefined goals, simple proto-games with ad-hoc rules often emerge, for example, placing objects on top of each other (create a tower) or an aiming-to-a-target shooting game. We propose an analysis of the emergence of such proto-games in terms of group exploration and exploitation. Specifically, we focus on cases of transition from exploration to exploitation underlying the discovery of a new form or rule. Based on Choreographer João Fiadeiro’s body of work, we describe these phase shifts as a distributed process composed of three stages: (1) Suggestion, (2) Recognition and (3) Confirmation. We provide detailed descriptions of game moments according to this model, demonstrating the distributed nature of collective creativity in free play.